Ambiguous Masculinities: Gender and Sexual Transgression in Contemporary Dance Works by Senegalese Men. Issue 3 (December 2019) - Swanson, Amy
Abstract: Contemporary dance in Senegal emerged and thrives at the interstices of the local and the global. Multiple expectations and values, of which gender and sexuality are no small part, converge at the site of creation and production, enlisting choreographers to navigate oftentimes conflicting ideologies. Based on ethnographic research, this article examines three works by Senegalese men that employ gender and sexual transgressions alongside the artists' seemingly contradictory verbal articulations of their work. Using the local-global entanglement as an analytical framework, I argue that these works offer ambiguous assemblages of masculinities that challenge conventional masculinity in Senegal, thereby elucidating the potentiality for contemporary dance to transcend singular meaning-making capacity.